Suppressing Dazl modulates tumorigenicity and stemness in human glioblastoma cells - Fengyu Zhang; Ruilai Liu; Haishi Zhang; Cheng Liu; Chunfang Liu; Yuan Lu (BMC Cancer, 2020)
Abstract Background Glioblastoma is devastating cancer with a high frequency of occurrence and poor survival rate and it is urgent to discover novel glioblastoma-specific antigens for the therapy. Cancer-germline genes are known to be related to the formation and progression of several cancer types by promoting tumor transformation. Dazl is one such germline gene and is up-regulated in a few germ cell cancers. In this study, we analyzed the expression of Dazl in human glioblastoma tissues and cells, and investigated its significance in proliferation, migration, invasion and chemoresistance of the glioblastoma cell lines. Methods We evaluated the expression of Dazl in different pathologic grades of glioblastoma tissues by immunohistochemistry. We assessed the expression of Dazl in glioblastoma cells and normal human astrocytes (NHA) cells by western blotting and RT-qPCR. Then we generated Dazl knockout glioblastoma cell lines using the CRISPR/Cas9 gene-editing technology to explore the cellular function of Dazl. We detected the proliferation and germline traits via CCK-8 assays and alkaline phosphatase staining, respectively. Boyden chamber assays were performed to measure glioblastoma cell migration and invasion. Crystal violet staining was used to determine the number of viable cells after the treatment of Doxorubicin and Temozolomide. Finally, we used subcutaneous xenograft studies to measure the growth of tumors in vivo. Results We found that Dazl was upregulated in glioblastoma tissues and glioblastoma cell lines. Dazl knockdown glioblastoma cells showed decreased cellular proliferation, migration, invasion, and resistance in vitro, and inhibited the initiation of glioblastoma in vivo. The glioblastoma cell lines A172, U251, and LN229 were found to express stem cell markers CD133, Oct4, Nanog, and Sox2. The expression of these markers was downregulated in Dazl-deficient cells. Conclusions Our results indicated that Dazl contributes to the tumorigenicity of glioblastoma via reducing cell stemness. Therefore, cancer-germline genes might represent a new paradigm of glioblastoma-initiating cells in the treatment of malignant tumors.